Selection signature analysis and genome-wide divergence of South African Merino breeds from their founders - Dzomba, E. F.; Van Der Nest, M. A.; Mthembu, J. N. T.; Soma, P; Snyman, M. A.; Chimonyo, M.; Muchadeyi, F. C. (Frontiers in Genetics, 2023)
Merino sheep are a breed of choice across the world, popularly kept for their wool and mutton value. They are often reared as a pure breed or used in crossbreeding and are a common component in synthetic breed development. This study evaluated genetic diversity, population structure, and breed divergence in 279 animals of Merino and Merino-based sheep breeds in South Africa using the Illumina Ovine SNP 50K BeadChip. The sheep breeds analysed included the three Merino-derived breeds of Dohne Merino (n = 50); Meatmaster (n = 47); and Afrino (n = 52) and five presumed ancestral populations of Merinos (Merino (n = 46); South African Merino (n = 10); and South African Mutton Merino (n = 8)); and the non-Merino founding breeds of Damara (n = 20); Ronderib Afrikaner (n = 17); and Nguni (n = 29). Highest genetic diversity values were observed in the Dohne Merino (DM), with Ho = 0.39 ± 0.01, followed by the Meatmaster and South African Merino (SAM), with Ho = 0.37 ± 0.03. The level of inbreeding ranged from 0.0 ± 0.02 (DM) to 0.27 ± 0.05 (Nguni). Analysis of molecular variance (AMOVA) showed high within-population variance (>80%) across all population categories. The first principal component (PC1) separated the Merino, South African Mutton Merino (SAMM), DM, and Afrino (AFR) from the Meatmaster, Damara, Nguni, and Ronderib Afrikaner (RDA). PC2 aligned each Merino-derived breed with its presumed ancestors and separated the SAMM from the Merino and SAM. The iHS analysis yielded selection sweeps across the AFR (12 sweeps), Meatmaster (four sweeps), and DM (29 sweeps). Hair/wool trait genes such as FGF12; metabolic genes of ICA1, NXPH1, and GPR171; and immune response genes of IL22, IL26, IFNAR1, and IL10RB were reported. Other genes include HMGA, which was observed as selection signatures in other populations; WNT5A, important in the development of the skeleton and mammary glands; ANTXR2, associated with adaptation to variation in climatic conditions; and BMP2, which has been reported as strongly selected in both fat-tailed and thin-tailed sheep. The DM vs. SAMM shared all six sweep regions on chromosomes 1, 10, and 11 with AFR vs. SAMM. Genes such as FGF12 on OAR 1:191.3–194.7 Mb and MAP2K4 on OAR 11:28.6–31.3 Mb were observed. The selection sweep on chromosome 10 region 28.6–30.3 Mb harbouring the RXFP2 for polledness was shared between the DM vs. Merino, the Meatmaster vs. Merino, and the Meatmaster vs. Nguni. The DM vs. Merino and the Meatmaster vs. Merino also shared an Rsb-based selection sweep on chromosome 1 region 268.5–269.9 Mb associated with the Calpain gene, CAPN7. The study demonstrated some genetic similarities between the Merino and Merino-derived breeds emanating from common founding populations and some divergence driven by breed-specific selection goals. Overall, information regarding the evolution of these composite breeds from their founding population will guide future breed improvement programs and management and conservation efforts.